EXPLORING THE IMPACT OF TEACHER PROFESSIONAL IDENTITY ON THE TEACHING OF NUMBER CONCEPTS IN THE FOUNDATION PHASE - Gugulethu Ncube; Phillip A. Kutame; Sithabile Ntombela; Oluwatoyin Ayodele Ajani (International Journal of Innovative Technologies in Social Science, 2025)
This qualitative study sort to understand the influence of teacher professional identity on teaching number concepts in the foundation phase. Twelve foundation phase teachers from the Johannesburg East District were purposively selected. Data was collected using in-depth interview schedule and observation tool and analysed thematically. The findings reveal that teacher professional identity has an influence on how teachers teach number concepts. The influence was either negative or positive. The positive identity manifested where teachers view themselves as pedagogical content knowledge specialists, in loco parentis, among others. Teachers who exhibited a positive teacher professional identity were characterised by enthusiasm, self-motivated, friendly, having a sense of competence and commitment. On the other hand, a negative teacher professional identity was characterised by teachers viewing themselves as teacher-administrators, the ‘l’ as a social worker, among others. In some scenarios, we noted that there was lack of synergy between the way teachers teach number concepts and the self-image. The self-image was not reflected in their teaching. We concluded that the manner in which teachers see themselves as teachers teaching number concepts plays a major role in shaping the teaching of number concepts in the foundation phase. We recommend that the employer invest in programs that will improve how teachers see themselves as teachers teaching number concepts.